2021
DOI: 10.3390/ph14080753
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenic Acid Accelerates Healing of Corneal Epithelium In Vitro and In Vivo

Abstract: Kynurenic acid (KYNA) is an endogenous compound with a multidirectional effect. It possesses antiapoptotic, anti-inflammatory, and antioxidative properties that may be beneficial in the treatment of corneal injuries. Moreover, KYNA has been used successfully to improve the healing outcome of skin wounds. The aim of the present study is to evaluate the effects of KYNA on corneal and conjunctival cells in vitro and the re-epithelization of corneal erosion in rabbits in vivo. Normal human corneal epithelial cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…It should be pointed out that KYNA is a beneficial compound in wound healing, since it was reported that KYNA prevents scarring and may be used as an anti-fibrogenic agent [10]. It was proved that kynurenine and its derivatives (e.g., KYNA) might be considered as effective wound healing agents in a rabbit ear scar model [11,12] Since KYNA has established health-promoting properties but its content in food is relatively low [1], a search to identify rich sources of natural KYNA is in progress. The obtained results indicate that the tested flax cultivars contained a maximum of 0.4 µg/g FW KYNA in the seeds.…”
Section: Kyna Synthesis In Flax Exposed To Tryptophan and Kynureninementioning
confidence: 99%
See 1 more Smart Citation
“…It should be pointed out that KYNA is a beneficial compound in wound healing, since it was reported that KYNA prevents scarring and may be used as an anti-fibrogenic agent [10]. It was proved that kynurenine and its derivatives (e.g., KYNA) might be considered as effective wound healing agents in a rabbit ear scar model [11,12] Since KYNA has established health-promoting properties but its content in food is relatively low [1], a search to identify rich sources of natural KYNA is in progress. The obtained results indicate that the tested flax cultivars contained a maximum of 0.4 µg/g FW KYNA in the seeds.…”
Section: Kyna Synthesis In Flax Exposed To Tryptophan and Kynureninementioning
confidence: 99%
“…Since obesity and cardiovascular diseases constitute increasing health problems in developing societies, it is justifiable to search for natural products that are effective in the prevention and treatment of these diseases. On the other hand, it was stated that KYNA improves the healing of skin wounds [10][11][12] and prevents the formation of scars [10]. Thus, two aspects of KYNA application should be considered: its systemic effect on the human body (e.g., on the digestive system) and its local action (e.g., for wound healing).…”
Section: Introductionmentioning
confidence: 99%
“…In T1DM, there was an upregulation of xanthurenic acid and kynurenic acid in the corneal stroma, suggesting dysregulation of kynurenine metabolism. Kynurenic acid is known to have antioxidant, anti-inflammatory, and anti-proliferative properties [ 99 , 100 ] and the kynurenine pathway has been linked to corneal endothelium health [ 101 ]. In T2DM, however, there was no increase in kynurenic acid and xanthurenic acid but a significant increase in nicotinate levels due to the modulation of tryptophan metabolism, with no increase in the metabolites in the kynurenine pathway.…”
Section: Diabetic Corneasmentioning
confidence: 99%
“…The beneficial wound healing effects of KYNA ( Table S7 ) after its external administration on the skin and cornea in rabbits are also worth mentioning [ 104 , 105 ]. It is worth noting that a clinical trial with the use of 0.5% KYNA dressing in people with skin scarring has already been successfully completed [ 106 ].…”
Section: Kynurenic Acid Supplementationmentioning
confidence: 99%
“…Detailed data on the health-promoting effects of KYNA administration in animals regardless of the route of administration are presented in Table S7 [ 26 , 87 , 90 , 93 , 94 , 95 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ].…”
Section: Kynurenic Acid Supplementationmentioning
confidence: 99%